(untitled) (AmeriQuests, 2017)
Aku no Hana (The Flowers of Evil) is a manga written and drawn by Shūzō Oshimi between 2009 and 2014. These 11 volumes, which sold more than 2,000,000 copies, were a commercial success, subsequently partially adapted into an animated Japanese television show of 13 episodes, which aired in 2013. Kasuga, the main character of the series, is an adolescent bored with his mediocre life in a rural village. Under the influence of his father, who is also a literature fanatic, he develops a passionate appreciation for Les Fleurs du Mal, even if his reading of the Japanese translation of this complex text does not permit a comprehension of it’s dark and erotic atmosphere. One day, finding himself alone in the classroom, he steals the mini-skirt of the most popular girl in the class, Sakei. The only witness to this perverse act is Nakamura, another girl in the class, who begins to torment Kasuga with the threat of revealing his sexual crime. Through the analysis of Baudelaire’s role in this manga, I hope to outline the French poet’s current reception in Japan, which, even if diminished, still exists in this country where French literature has become less popular than it was a half century ago.